Kinetic Energy Cascade in the Frequency Domain from Satellite Products - Qianqian Geng; Xin Su; Ru Chen; Gang Huang; Wanli Shi (Remote Sensing)
Multiscale oceanic motions continuously transfer kinetic energy across various spatiotemporal scales through kinetic energy cascade. Satellite altimetry offers long-term daily ocean data at 0.25-degree resolution, enabling the analysis of energy cascades in both wavenumber and frequency domains. While energy cascade studies in the wavenumber domain are well-developed, frequency domain analyses remain limited. In this study, using 24 years of velocity data from satellite altimetry, we analyze the surface frequency-domain kinetic energy cascade primarily using the coarse-graining method. Compared to other approaches in literature, the coarse-graining approach shows superiority in diagnosing energy cascade in the frequency domain. Using this approach in the Kuroshio Extension region, we compare the spatiotemporal variability of energy cascades between the frequency and wavenumber domains. A pronounced low-frequency forward cascade, distinct from the wavenumber domain results, is identified. We propose a theory linking this low-frequency forward cascade with eddy generation through eddy–mean flow interactions. Significant variability is also observed in frequency domain energy cascades. Further analysis shows that wind forcing only plays a minor role in modulating the temporal variability of the energy cascade. Our findings are crucial for evaluating the model’s fidelity and advancing investigation of climate variability from the perspective of energy transfer.